2015
DOI: 10.1158/1078-0432.ccr-15-0304
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Trial of the Anti-KIR Antibody IPH2101 and Lenalidomide in Patients with Relapsed/Refractory Multiple Myeloma

Abstract: PURPOSE Natural killer (NK) cells may play an important role in the immune response to multiple myeloma (MM); however, MM cells express killer immunoglobulin-like receptor (KIR) ligands to prevent NK cell cytotoxicity. Lenalidomide can expand and activate NK cells in parallel with its direct effects against MM; however, dexamethasone may impair these favorable immunomodulatory properties. IPH2101, a first-in-class anti-inhibitory KIR antibody, has acceptable safety and tolerability in MM as a single agent. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
127
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(129 citation statements)
references
References 32 publications
2
127
0
Order By: Relevance
“…This ability to influence adaptive immunity as well as their innate tumor cytolytic capability implicates NK cells as key effectors of antitumor immunity. As a result, the blockade of immunoregulatory NK cell checkpoint receptors has garnered significant interest (32)(33)(34). Agents (e.g., lirilumab) targeting NK cell inhibitory receptors, such as killer cell immunoglobulin-like receptor (KIR), are the subject of intense preclinical/clinical investigation as a monotherapy or in combination with other checkpoint inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…This ability to influence adaptive immunity as well as their innate tumor cytolytic capability implicates NK cells as key effectors of antitumor immunity. As a result, the blockade of immunoregulatory NK cell checkpoint receptors has garnered significant interest (32)(33)(34). Agents (e.g., lirilumab) targeting NK cell inhibitory receptors, such as killer cell immunoglobulin-like receptor (KIR), are the subject of intense preclinical/clinical investigation as a monotherapy or in combination with other checkpoint inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…Further, it should be appreciated that inhibitory KIRs are expressed on a subset of effector and/or memory CD4 + and CD8 + T cells in addition to NK cells, so KIR blockade might augment the antitumour activity of T cells in addition to NK cells. Phase I and Phase II trials in patients with acute myeloid leukaemia (AML) or multiple myeloma have demonstrated that treatment with anti-KIR is safe and has minimal side effects [113][114][115] . Although these early trials using anti-KIR as a monotherapy have not demonstrated significant efficacy, one might envisage synergy when it is combined with CTLA4 or PD1 blockade, which are known to induce systemic induction of pro-inflammatory cytokines that may further boost NK cell function.…”
Section: Anergic Statementioning
confidence: 99%
“…These checkpoint molecules are also crucial in protecting GBM stem cells (120). other checkpoint molecules under investigation include T-cell immunoglobulin domain and mucin domain 3 (TiM3) (122), lymphocyte activation gene-3 (LAG3) (123), killer-cell immunoglobulin-like receptor (KiR) (124) and V-domain ig suppressor of T-cell activation (VisTA) (125). checkpoint inhibitors are now in widespread clinical use against a wide variety of cancer types.…”
Section: Immune Checkpoint Inhibitors: Monotherapymentioning
confidence: 99%